Improving HIV testing, linkage, and retention in care among South African men through U = U messaging: A study protocol for two sequential hybrid type 1 effectiveness-implementation randomized controlled trials - Medina-Marino, Andrew; Sibanda, Nkosiyapha; Putt, Mary; Joseph Davey, Dvora; Smith, Phillip; Thirumurthy, Harsha; Bekker, Linda-Gail; Buttenheim, Alison (PloS one, 2024)
Increasing HIV testing and treatment coverage among people living with HIV (PLHIV) is essential for achieving global HIV epidemic control. However, compared to women, cis-gender heterosexual men living with HIV are significantly less likely to know their HIV status, initiate anti-retroviral therapy (ART) and achieve viral suppression. This is particularly true in South Africa, where men are also at increased risk of mortality resulting from AIDS-related illnesses. While there is growing knowledge of Treatment as Prevention or the concept Undetectable = Untransmittable (U = U) among PLHIV in Western and high-income countries, the reach and penetration of the U = U message in sub-Saharan Africa remains limited, and few studies have evaluated the impact of accessible and relatable U = U messages on ART initiation and adherence. To address these gaps, rigorous evaluations of interventions that incorporate U = U messages are needed, especially among men in high prevalence settings. Building on our U = U messages that we previously developed for men using behavioral economics insights and a human-centered design, we will conduct two sequential hybrid type 1 effectiveness-implementation trials to evaluate the impact of U = U messages on men's uptake of community-based HIV testing and ART initiation (Trial 1), and retention in care and achievement of viral suppression (Trial 2). For trial 1, a cluster randomized trial will be implemented with HIV testing service site-days (each day at one testing site) randomized to U = U or standard-of-care (SoC) messages inviting men to test for HIV. For trial 2, an individual-level randomized control trial will be implemented, with men initiating ART at six government clinics randomized to receive U = U counselling or SoC treatment adherence messaging. We will incorporate a multi-method evaluation to inform future implementation of U = U messaging interventions. The study will be conducted in the Buffalo City Metro Health District of the Eastern Cape Province and in the Cape Town Metro Health District in the Western Cape Province in South Africa. These trials are the first to rigorously evaluate the impact of U = U messaging on HIV testing uptake, ART initiation and achievement of viral suppression among African men. If effective, these messaging interventions can shape global HIV testing, treatment and adherence counselling guidelines and practices.